Application of the distally based sural neurocutaneous flaps in the management of foot and ankle defects in patients with diabetic foot - Dai, Jiezhi; Zhou, Yu; Mei, Shasha; Chen, Hua (Frontiers in Endocrinology, 2022)
Background We report our experience on the use of a distally based sural flap for soft tissue reconstruction of foot and ankle defects in patients with diabetic foot. Methods The actual study is a retrospective, open, non-controlled, and clinical study of 25 patients treated with diabetic foot on whom reconstruction with distally based sural neurocutaneous flaps was performed from May 2019 to December 2021. Results The mean age was 64.9 years, and there were 15 male and 10 female patients. The mean follow-up was 9.8 months, which ranged from 6 to 12 months. The size of the flaps ranged from 6 × 5 to 15 × 9 cm2. Twenty-two of the 25 flaps survived intact with sufficient blood supply. Two cases had a small superficial necrosis, which was resolved after a change of daily dressing and was heeled eventually. In one case, partial necrosis was observed that was managed with minor revision and the use of split-thickness skin graft. Conclusions The distally based sural flap is considered to be useful for reconstruction of foot and ankle defects in patients with diabetic foot.